Identification of a novel de novo pathogenic variant in GFAP in an Iranian family with Alexander disease by whole-exome sequencing - Katayoun Heshmatzad; Niloofar Naderi; Tannaz Masoumi; Hamidreza Pouraliakbar; Samira Kalayinia (European Journal of Medical Research, 2022)
Abstract Background Alexander disease (AxD) is a rare leukodystrophy with an autosomal dominant inheritance mode. Variants in GFAP lead to this disorder and it is classified into three distinguishable subgroups: infantile, juvenile, and adult-onset types. Objective The aim of this study is to report a novel variant causing AxD and collect all the associated variants with juvenile and adult-onset as well. Methods We report a 2-year-old female with infantile AxD. All relevant clinical and genetic data were evaluated. Search strategy for all AxD types was performed on PubMed. The extracted data include total recruited patients, number of patients carrying a GFAP variant, nucleotide and protein change, zygosity and all the clinical symptoms. Results A novel de novo variant c.217A > G: p. Met73Val was found in our case by whole-exome sequencing. In silico analysis categorized this variant as pathogenic. Totally 377 patients clinically diagnosed with juvenile or adult-onset forms were recruited in these articles, among them 212 patients were affected with juvenile or adult-onset form carrier of an alteration in GFAP. A total of 98 variants were collected. Among these variants c.262C > T 11/212 (5.18%), c.1246C > T 9/212 (4.24%), c.827G > T 8/212 (3.77%), c.232G > A 6/212 (2.83%) account for the majority of reported variants. Conclusion This study highlighted the role of genetic in AxD diagnosing. It also helps to provide more information in order to expand the genetic spectrum of Iranian patients with AxD. Our literature review is beneficial in defining a better genotype–phenotype correlation of AxD disorder.